Assessment of mode of delivery and predictors of emergency caesarean section among women living with HIV in a matched‐pair setting with women from the general population in Denmark, 2002−2014. Issue 10 (24th May 2017) - Ørbæk, M; Thorsteinsson, K; Helleberg, M; Moseholm, E; Katzenstein, TL; Storgaard, M; Johansen, IS; Pedersen, G; Weis, N; Lebech, A‐M
Abstract : Objectives: We aimed to assess mode of delivery and predictors of emergency caesarean section (EmCS) in women living with HIV (WLWH) in a matched‐pair setting with women from the general population (WGP) in Denmark. Further, we analysed birth plan in WLWH. Methods: All WLWH giving birth to live‐born children from 2002 to 2014 were included in the study. Data were retrieved from medical records and national registries. WLWH were matched 1:5 by age, birth year, parity and ethnicity to WGP. Multivariate logistic regression was used to estimate predictors. Results: We included 389 WLWH and 1945 WGP in the study. At delivery, all WLWH were on antiretroviral therapy and 85.6% had HIV RNA <40 HIV‐1 RNA copies/mL. Mean age was 32.7 years [95% confidence interval (CI) 32.1–33.2 years]. Mode of delivery differed significantly between WLWH and WGP [vaginal delivery, 33.4% versus 73.3%, respectively; elective caesarean section (ECS), 40.6% versus 9.7%, respectively; EmCS, 26% versus 17%, respectively; P < 0.0001]. Age > 40 years [adjusted odds ratio (aOR) 2.3; 95% CI 1.5–3.5], asphyxia (aOR 3.2; 95% CI 2.4–4.1), delivery during the evening and at night [aOR 2.3 (95% CI 1.7–3.0) and aOR 2.0 (95% CI 1.5–2.7), respectively], preterm delivery (aOR 3.8; 95% CI 2.6–5.6) and premature rupture of membranes (aOR 3.0; 95% CI 2.1–4.4) predicted EmCS. WLWH had a higher risk of EmCS compared with WGP [2002–2006, aOR 2.0 (95% CI 1.2–3.3); 2007–2008, aOR 2.9 (95% CI 1.4–5.9); 2009–2014, aOR 2.6 (95% CI 1.7–3.9)]. After 2007, more than half of WLWH planned to deliver vaginally. Prior caesarean section was associated with ECS (aOR 11.0; 95% CI 4.5–26.8). No mother‐to‐child transmission occurred. Conclusions: Increasing numbers of WLWH deliver vaginally. Despite virological suppression, more WLWH plan and deliver by ECS than WGP. WLWH had a twofold higher risk of EmCS compared with WGP.